Paul’s Style and the Problem of the Pastoral Letters: Assessing Statistical Models of Description and Inference - Pracht Erich Benjamin; McCauley Thomas (Open Theology)
In this study, we combine the core competencies of a New Testament scholar and a mathematician to conduct a stylometric analysis of the Pauline and Pastoral Letters based on 18 epistolary modes of discourse, which we argue are at least as stylistically relevant as traditional features such as term frequencies. By focusing on features of this type, we apply discrete probability models – namely, the binomial, Poisson, and negative binomial distributions – to determine which ones are the best fit for each feature. With our approach, we have found a way to utilize Paul’s authentic letters as a standard of measurement by which the style(s) of the Pastorals can be compared, an essential first step to statistical inference that is generally lacking in Pauline stylometry. With few exceptions, we find that the Pastoral Letters do not contain stylistic differences with the authentic Paulines at a statistically significant level, a finding that disputes many previous studies (especially in the qualitative tradition) that assume stylistic difference, but which is in line with an emerging trend in computational analyses of the Pauline and Pastoral Letters.